FORMULATION AND EVALUATION OF TOPICAL HERBAL GEL FOR TREATMENT OF ACNE - K R, Sushmitha; Kopparam, Manjunath; Kulkarni, Suresh V (Journal of Biomedical and Pharmaceutical Research, 2019)
The objective of the study was to develop a topical herbal gel for the treatment of mild acne vulgaris. Aqueous extracts Withania somnifera formulated using different gelling agent like carbopol-934, Xanthan gum, & HPMC K100 M. Nine formulations of the gel were prepared by varying the proportions of polymer and evaluated for their physicochemical properties like appearance, pH, spreadability, viscosity, assay, and microbial assay. FTIR studies reveals that there was no interaction between the Withania somnifera and selected polymers Carbopol 934, Xanthan gum and HPMC K 100 M. In vitro drug diffusion studies showed percentage CDR of 100.16 % at the end of 3 hours. The microbial assay of all the formulations demonstrated better inhibitory activity against Staphylococcus epidermidis compared to the marketed clindamycin phosphate gel. The stability study carried out of the selected gel F2 at room temperature and 40 ± 2 °C / 75 ± 5 % RH was found to be stable for a period of 45 days in terms of drug content, physical appearance and pH etc. Based on these results, Formulation F2 containing 1.5 % carbopol-934 was selected as best formulation. Key words: Herbal gel, Withania somnifera, In vitro diffusion, Zone of inhibition.